Environmental migrations. Some critical remarks on an ambiguous legal definition (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Environmental migrations are at the center of a doctrinal debate that is divided over two main issues: the configuration of the criteria for the relevance of the ‘environmental factor’ and, from this, the possibility of making this hypothesis an autonomous case within the framework of international protection systems. In the folds of this discussion, theoretical and systemic profiles emerge. The former suggest dwelling on the ambiguous overlap between nature and environment hinged on the definition of environmental migration. The others point to the possibility of measuring, through the lens of the relationship between migration and environment, some of the aporias that run through the contemporary system of migration law.
Keywords: Law; environment; migrations; nature; society